2022
DOI: 10.1021/acs.oprd.1c00436
|View full text |Cite
|
Sign up to set email alerts
|

Commercial-Scale Visible Light Trifluoromethylation of 2-Chlorothiophenol Using CF3I Gas

Abstract: Despite the growth of photoredox methods in academia, application of photoredox at scale in the pharmaceutical and fine chemical industries has been slow. In this report, a photoredox trifluoromethylation of a thiophenol was modified from the original literature report, and the mechanism was investigated to define the key scale-up parameters. The mechanistic insight was leveraged in the design and execution of two different reactor designs: an LED-based plug flow photoreactor and a laser-based continuous stirr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Prior to this disclosure there had been pioneering work on the scale-up of visible-light-mediated processes from Merck, most notably for the synthesis of elbasvir . Our report and further outstanding contributions by Merck, AbbVie, , and others have clearly shown how visible light can be effectively used at manufacturing scale and in a Current Good Manufacturing Practices (cGMP) environment. Our system was operated continuously for 48 h, consuming a total of 1.2 kg of 30 to yield 31 in 60–65% assay yield.…”
Section: Lifa Collaboration Studiesmentioning
confidence: 81%
“…Prior to this disclosure there had been pioneering work on the scale-up of visible-light-mediated processes from Merck, most notably for the synthesis of elbasvir . Our report and further outstanding contributions by Merck, AbbVie, , and others have clearly shown how visible light can be effectively used at manufacturing scale and in a Current Good Manufacturing Practices (cGMP) environment. Our system was operated continuously for 48 h, consuming a total of 1.2 kg of 30 to yield 31 in 60–65% assay yield.…”
Section: Lifa Collaboration Studiesmentioning
confidence: 81%
“…At this early stage in the development of the field, most examples of highly asymmetric photocatalytic reactions have been proof-ofprinciple academic investigations, and these insights have yet to be translated to commercial applications. As the pharmaceutical industry in particular becomes more interested in the scale-up of photocatalytic processes, 426,427 issues concerning maximization of quantum yield and light flux 428 may become more important than they have been to date. Despite the impressive advances that have emerged in the field of asymmetric photocatalysis in recent years, many challenges remain unsolved, perhaps the most important of which is the need for generality.…”
Section: Discussionmentioning
confidence: 99%
“…Besides passive microreactors (which exploit the flow energy delivered by the pumps to induce mixing), active microreactors that utilize external energy are also commonly employed, particularly for scaling heterogeneous chemistry up. Multiple types of active continuous reactors have been reported, such as rotating disk reactors, 92–94 oscillatory flow reactors, 95–97 thin-film rotating reactors, 98 CSTR 99,100 and ultrasonic reactors. 101,102 To demonstrate the advantages of such flow chemistry technology, Van der Schaaf and Noël et al reported a high-throughput photochemical rotor-stator spinning disk reactor (pRS-SDR) to enhance the gas–liquid mass transfer and perform a large-scale gas–liquid photooxygenation of α-terpinene ( 19.1 ).…”
Section: Scalabilitymentioning
confidence: 99%